2019
DOI: 10.1371/journal.pone.0209736
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of women’s experiences of antenatal and intrapartum care: The need for a woman-centred approach in the Peruvian Amazon

Abstract: ObjectiveTo explore women’s experiences and perceptions of antenatal and intrapartum care in the Peruvian Amazon, including their perceived motivators, enablers and barriers to accessing care.DesignInterpretive descriptive qualitative study using semi-structured face-to-face interviews.SettingPrimary healthcare centre, Iquitos, Peru.ParticipantsWomen (n = 20) attending the healthcare centre who had given birth in the past 6 months.MeasuresInterviews were conducted using a female interpreter, transcribed clean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In-keeping with findings from qualitative research in Iquitos, antenatal care providers must ensure that all women feel involved in decision making about their birth [23]. Women in this study also expressed a desire for more written information to take home, reflecting the perceptions of other women from Iquitos [23]. More written pregnancy-related information could be added to women's…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In-keeping with findings from qualitative research in Iquitos, antenatal care providers must ensure that all women feel involved in decision making about their birth [23]. Women in this study also expressed a desire for more written information to take home, reflecting the perceptions of other women from Iquitos [23]. More written pregnancy-related information could be added to women's…”
Section: Discussionmentioning
confidence: 72%
“…The lower frequency of second-time services received out of routine appointments could be due to women not being able return to healthcare centres to independently seek these services. This could be due to childcare, employment or inconvenient opening hours, as previously demonstrated in qualitative studies investigating barriers to accessing ANC amongst Peruvian women [23,62]. Such services might be received more frequently if they were provided within routine appointments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Marsland et al, conducted a study about women's perceptions of antenatal and IPC in Loreto; women reported free appointments facilitated antenatal care attendance and IPC was often poor, including discontinuity of care [35]. Westgard et al, also reported that women in rural Peru understood the importance of seeking obstetric care, particularly with complicated pregnancies [36].…”
Section: Introductionmentioning
confidence: 99%